Seed compositional studies of some species of Papilionoideae (Leguminosae) native to Argentina - Maestri, Damian (2002)
Seeds of 17 wild leguminous species belonging to the Papilionoideae subfamily were analysed for their proximate, fatty acid and sterol compositions. Centrosema virginianum, Tipuana tipu, Adesmia volckmanni and some species of Desmodium contained high amounts (>300 g kg-1) of protein. Geoffroea decorticans and Clitoria cordobensis were noteworthy for their high oil content (>350 g kg-1). The seed lipids had a high proportion of unsaturated (oleic and linoleic mainly) fatty acids. Linolenic acid had the highest value in Adesmia volckmanni (25.4% of total fatty acids). β-Sitosterol was the major component of the sterol fraction. Chemical analyses indicated that all species studied are suitable sources of animal feed. © 2002 Society of Chemical Industry.